Carbon Amendments Influence Composition and Functional Capacities of Indigenous Soil Microbiomes - Dundore-Arias, José Pablo; Castle, Sarah C.; Felice, Laura; Dill-Macky, Ruth; Kinkel, Linda L. (Frontiers in Molecular Biosciences, 2020)
Soil nutrient amendments are recognized for their potential to improve microbial activity and biomass in the soil. However, the specific selective impacts of carbon amendments on indigenous microbiomes and their metabolic functions in agricultural soils remain poorly understood. We investigated the changes in soil chemical characteristics and phenotypes of Streptomyces communities following carbon amendments to soil. Mesocosms were established with soil from two field sites varying in soil organic matter content (low organic matter, LOM; high organic matter, HOM), that were amended at intervals over nine months with low or high dose solutions of glucose, fructose, malic acid, a mixture of these compounds, or water only (non-amended control). Significant shifts in soil chemical characteristics and antibiotic inhibitory capacities of indigenous Streptomyces were observed in response to carbon additions. All high dose carbon amendments consistently increased soil total carbon, while amendments with malic acid decreased soil pH. In LOM soils, higher frequencies of Streptomyces inhibitory phenotypes of the two plant pathogens, Streptomyces scabies and Fusarium oxysporum, were observed in response to soil carbon additions. Additionally, to determine if shifts in Streptomyces functional characteristics correlated with microbiome composition, we investigated whether shifts in functional characteristics of soil Streptomyces correlated with composition of soil bacterial communities, analyzed using 16S rRNA gene sequencing. Regardless of dose, community composition differed significantly among carbon-amended and non-amended soils from both sites. Carbon type and dose had significant effects on bacterial community composition in both LOM and HOM soils. Relationships among microbial community richness (observed species number), diversity, and soil characteristics varied among soils from different sites. These results suggest that manipulation of soil resource availability has the potential to selectively modify the functional capacities of soil microbiomes, and specifically to enhance pathogen inhibitory populations of high value to agricultural systems.